Evaluasi Potensi Ekstrak Etanol Daun Kencur (Kaempferia galanga L.) sebagai Antimikroba terhadap Propionibacterium acnes melalui Teknik Disk Diffusion - Sawal, Rizky Ardian Hartanto; Rahayu, Noel Asri (Jurnal Farmasi & Sains Indonesia, 2023)
The galangal plant, which many people still don't know about, has a variety of interesting benefits. Among other things, kencur leaves contain chemical compounds such as flavonoids and essential oils which have antimicrobial properties. This study aims to activate the antibacterial activity of ethanol extract of kencur leaves against Propionibacterium acnes, as well as to measure how effective it is at different concentrations. The extraction process uses 96% ethanol solvent with the Remaceration method, which is then accompanied by phytochemical screening and TLC tests to strengthen the results. Antibacterial activity tests were carried out using the disc diffusion method at concentrations of 0.3%, 0.6%, 1.2% and 2.4%. The results show the inhibition zone at each concentration, namely 6.86 mm, 8.4 mm, 9.8 mm, and 10.96 mm. Phytochemical analysis identified secondary metabolite compounds such as tannins, saponins and flavonoids with Rf values of 0.925 each; 0.825; and 0.8125. Statistical analysis showed a significant difference between concentrations of 0.3% and 1.2%.